2019
DOI: 10.1155/2019/9574045
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi-Danshen Decoction Ameliorates Adenine-Induced Chronic Kidney Disease by Modulating Mitochondrial Dynamics

Abstract: Chronic kidney disease (CKD) is a leading public health problem with high morbidity and mortality. However, the therapies remain limited. Traditional Chinese medicine (TCM) has been used for treating kidney disease for thousands of years and is an effective alternative treatment for CKD patients in China and other Asian countries. In the present study, we aimed to investigate the effect and mechanism of Huangqi-Danshen decoction (HDD), a TCM herbal decoction, on treating CKD. CKD rat model was induced by addin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Previous pharmacological studies have supported that JPYS can improve renal function and kidney injury in CKD rats [911] and can stimulate the transcriptional expression of EPO in cultured kidney HEK293T cells [12]. Besides, the extract of Astragali Radix and Salviae Miltiorrhizae Radix et Rhizoma deriving from JPYS also has been found to ameliorate adenine-induced CKD rats [13]. These findings confirm the beneficial role of JPYS for treatment of CKD anemia.…”
Section: Introductionsupporting
confidence: 64%
“…Previous pharmacological studies have supported that JPYS can improve renal function and kidney injury in CKD rats [911] and can stimulate the transcriptional expression of EPO in cultured kidney HEK293T cells [12]. Besides, the extract of Astragali Radix and Salviae Miltiorrhizae Radix et Rhizoma deriving from JPYS also has been found to ameliorate adenine-induced CKD rats [13]. These findings confirm the beneficial role of JPYS for treatment of CKD anemia.…”
Section: Introductionsupporting
confidence: 64%
“…According to TCM theory, Qi deficiency and blood stasis (Qi-Xu-Xue-Yu) runs through the CKD process (Liu et al, 2019). HDD is composed of Astragali Radix (Huang-qi) served as replenishing Qi and Salviae Miltiorrhizae Radix et Rhizoma (Dan-shen) served as activating blood, and is one of the most common used drug pair in clinical treatment of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…All the botanical names are recorded and can be validated using . The HDD water extract was prepared as previously described (Liu et al, 2019). High-performance liquid chromatography–mass spectrometry (HPLC-MS) analysis was conducted to confirm the quality of the HDD extract, as indicated in Supplementary Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) plays a unique role in the treatment of many diseases, and a growing body of evidence has shown that TCM is increasingly being used for preventing CKD and anemia [8][9][10]. Jian-Pi-Yi-Shen improved the anemia symptoms by increasing the serum EPO level and hypoxia inducible factor (HIF)-α protein in 5/6 nephretomized rats [11,12].…”
Section: Introductionmentioning
confidence: 99%